Konversi Agama dalam Masyarakat Desa Sembulung Kecamatan Cluring Kabupaten Banyuwangi - Obianto, Agung (IAI Darussalam, 2018)
The purpose of this study is to: 1) Describe the understanding of the people of Sembulung Village Cluring district Banyuwangi district about religious conversion. 2) Describe the factors causing the conversion of religion to the people of Sembulung Village Cluring District Banyuwangi District. 3) Describe the process of conversion of religion to the people of Sembulung Village Cluring District Banyuwangi District. This type of research is case study research. Research location Sembulung Village Cluring district Banyuwangi district. The data source used primary and secondary. Data Collection Technique used observation, interview, documentation. The data analysis used is interactive model analysis.The results of this study indicate that: 1) Understanding the conversion of religion from the villagers of Sembulung sub-district Cluring religious converts, ie moving beliefs, converting to other beliefs. 2) There are two factors that cause the conversion process of religion, namely the factor of marriage and motivation factor. 3) The conversion process of religion to the villagers of Sembulung sub-district Cluring takes place in five periods, ie period of calm, period of unrest, the period of conversion, the period of calm or second calm period, and period of conversion of new religion.